The Phase-I trigger readout electronics upgrade of the ATLAS Liquid Argon calorimeters. (1st May 2022) - Aad, G.; Akimov, A.V.; Al Khoury, K.; Aleksa, M.; Andeen, T.; Anelli, C.; Aranzabal, N.; Armijo, C.; Bagulia, A.; Ban, J.; Barillari, T.; Bellachia, F.; et al.
Abstract: The Phase-I trigger readout electronics upgrade of the ATLAS Liquid Argon calorimeters enhances the physics reach of the experiment during the upcoming operation at increasing Large Hadron Collider luminosities. The new system, installed during the second Large Hadron Collider Long Shutdown, increases the trigger readout granularity by up to a factor of ten as well as its precision and range. Consequently, the background rejection at trigger level is improved through enhanced filtering algorithms utilizing the additional information for topological discrimination of electromagnetic and hadronic shower shapes. This paper presents the final designs of the new electronic elements, their custom electronic devices, the procedures used to validate their proper functioning, and the performance achieved during the commissioning of this system.